Arizona Study of Aging and Neurodegenerative Disorders and Brain and Body Donation Program. Issue 4 (26th January 2015) - Beach, Thomas G.; Adler, Charles H.; Sue, Lucia I.; Serrano, Geidy; Shill, Holly A.; Walker, Douglas G.; Lue, LihFen; Roher, Alex E.; Dugger, Brittany N.; Maarouf, Chera; Birdsill, Alex C.; Intorcia, Anthony; et al.
<x xml:space="preserve">Abstract</x> The Brain and Body Donation Program (BBDP) at Banner Sun Health Research Institute (http://www.brainandbodydonationprogram.org) started in 1987 with brain‐only donations and currently has banked more than 1600 brains. More than 430 whole‐body donations have been received since this service was commenced in 2005. The collective academic output of the BBDP is now described as the Arizona Study of Aging and Neurodegenerative Disorders (AZSAND). Most BBDP subjects are enrolled as cognitively normal volunteers residing in the retirement communities of metropolitan Phoenix, Arizona. Specific recruitment efforts are also directed at subjects with Alzheimer's disease, Parkinson's disease and cancer. The median age at death is 82. Subjects receive standardized general medical, neurological, neuropsychological and movement disorders assessments during life and more than 90% receive full pathological examinations by medically licensed pathologists after death. The Program has been funded through a combination of internal, federal and state of Arizona grants as well as user fees and pharmaceutical industry collaborations. Subsets of the Program are utilized by the US National Institute on Aging Arizona Alzheimer's Disease Core Center and the US National Institute of Neurological Disorders and Stroke National Brain and Tissue Resource for Parkinson's Disease and Related Disorders. Substantial funding has also been received from the Michael J. Fox Foundation for Parkinson's Research. The Program has made rapid autopsy a priority, with a 3.0‐hour median post‐mortem interval for the entire collection. The median RNA Integrity Number (RIN) for frozen brain and body tissue is 8.9 and 7.4, respectively. More than 2500 tissue requests have been served and currently about 200 are served annually. These requests have been made by more than 400 investigators located in 32 US states and 15 countries. Tissue from the BBDP has contributed to more than 350 publications and more than 200 grant‐funded projects.